Students difficulties in learning the Javanese language: A case study at SMA Negeri 1 Kasiman, Bojonegoro, East Java, Indonesia - Devista, Nadia Lilia; Sukoyo , Joko (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2024)
Students at SMA Negeri 1 Kasiman face significant challenges in mastering the Javanese language. This research aims to pinpoint the specific difficulties encountered in Javanese language studies. The research employed a qualitative case study approach, focusing on students from SMA Negeri 1 Kasiman. Data were gathered through interviews, documentation, and questionnaires. The analysis was conducted using an interactive model, encompassing data reduction, data display, and drawing conclusions. Findings indicated that students struggle with aksara Jawa (23%), unggah-ungguh basa (21%), tembang macapat (13%), geguritan (10%), cerkak (10%), pranatacara (14%), and drama (9%). This highlights that the most challenging area is aksara Jawa, while drama poses the least difficulty. Contributing factors to these difficulties include insufficient time allocated for the subject and unengaging, uncreative, and non-innovative teaching methods and materials.